The impossible trinity - from the policy trilemma to the policy quadrilemma - Joshua Aizenman (University of California, Economics Department, 2011)
The policy Trilemma (the ability to accomplish only two policy objectives out of financial integration, exchange rate stability and monetary autonomy) remains a valid macroeconomic framework. The financial globalization during 1990s-2000s reduced the weighted average of exchange rate stability and monetary autonomy. An unintended consequence of financial globalization is the growing exposure of developing countries to capital flights, and deleveraging crises. The significant costs associated with these crises added financial stability to the Trilemma policy goals, modifying the Trilemma framework into the policy Quadrilemma. Emerging markets frequently coupled their growing financial integration with sizable hoarding of reserves, as means of self-insuring their growing exposure to financial turbulences. The global financial crisis of 2008-9 illustrated both the usefulness and the limitations of hoarding reserves as a selfinsurance mechanism. The massive deleveraging initiated by OECD countries in 2008 may provide the impetus for some emerging markets to impose soft capital controls in the form of regulations that restrain inflows of short terms funds. While modifying the global financial architecture to deal with the challenges of the 21th Centaury remains a work in progress, the extended Trilemma framework keeps providing useful insights about the trade-offs and challenges facing policy makers, investors, and central banks.
Keywords: F02; F31; F33; 330